IMPLEMENTASI SISTEM INFORMASI BIMBINGAN KONSELING BERBASIS WEB DALAM MENINGKATKAN EFEKTIVITAS LAYANAN BK DI SMP NEGERI 1 BAE KUDUS - Nur Robiatul Adawiyah; Arif Setiawan (LPPM ITB AAS Indonesia Surakarta, 2026)
The advancement of information technology has driven educational institutions to enhance the quality of their services, including Guidance and Counseling (GC). At SMP Negeri 1 Bae Kudus, GC services are still carried out using conventional methods, encompassing counseling submissions, documentation, and reporting activities. This situation leads to several challenges, such as delays in case handling, potential data loss, and difficulties in tracking students’ counseling histories.This Field Work Practice aims to design and implement a web-based Guidance and Counseling Information System to improve the effectiveness, efficiency, and transparency of GC services at SMP Negeri 1 Bae Kudus. The system is developed using the System Development Life Cycle (SDLC) with the waterfall model, which consists of requirement analysis, system design, implementation, testing, and system maintenance. The proposed system enables students to submit counseling requests online, while guidance counselors can manage counseling schedules, document counseling outcomes, maintain students’ counseling records, and automatically generate reports. The implementation of this web-based system is expected to streamline GC service processes, enhance the performance of guidance counselors, and support the digital transformation of educational services in response to the evolving information technology era.